An accelerated testing protocol for assessing microbially induced concrete deterioration during the bacterial attachment phase. (November 2019) - Erbektas, Ali Riza; Isgor, O. Burkan; Weiss, W. Jason
Abstract: This paper presents a test procedure that has been developed to specifically aim at assessing the performance of cementitious materials and antimicrobial additives during the bacterial attachment phase (Stage 2) of Microbially Induced Corrosion of Concrete (MICC). The test controls the pH associated with Stage 2 of MICC by using neutrophilic sulfur-oxidizing bacteria. The pH, sulfate concentration, optical density of the exposure solution, and microscopic observations on paste samples were used to assess microbial colonization. Paste deterioration and effectiveness of admixed and/or topically applied antimicrobial additives were evaluated by investigating the reduction in flexural strength, calcium leaching, and microstructural changes. It was shown that the proposed method is practical, realistic, and safe, and captures the effectiveness of antimicrobial additives during the bacterial attachment phase of MICC.